A NEW GENUS OF ELEPHANT FISHES (HOLOCEPHALI: CALLORHINCHIDAE) FROM THE UPPER CALLOVIAN OF THE VOLGA RIGION NEAR SARATOV, RUSSIA - Popov E.V. (My University, 2003)
Duffinodus nikolaii gen. et sp. nov., a new genus of elephant fishes (Chimaeroidei, Callorhinchidae) based on the right mandibular dental plate and the left vomerine plate from the Middle Jurassic (Upper Callovian, Quenstedticeras lamberti Ammonite Zone) from the Dubki quarry in the vicinities of Saratov (Saratov Province, Russia) is described. An emended diagnosis for the family Callorhinchidae Garman, 1901 based on dental plates is presented. The family consists of four or six genera: Callorhinchus Lacépède, 1798, Brachymylus Woodward, 1892, Pachymylus Woodward, 1892, Duffinodus gen. nov., ?Eomanodon Ward et Duffin, 1989 and ?Bathytheristes Duffin, 1995. A modified morphological nomenclature of the chimaeroid dentition is proposed.
Keywords: Callovian; Mesozoic::Jurassic::Middle::Callovian; Мезозой::Юрская::Средний::Келловейский